PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN DAN KANDUNGAN SAPONIN PADA DUA VARIETAS TANAMAN GENDOLA (Basella sp) - Listin Fitrianah; Siti Fatimah; Yunin Hidayati (Universitas Trunojoyo Madura, 2012)
The need for raw materials increase with increasing drug utilization of traditional medicine is increasing. Gendola is one type of potential medicinal plants, which have two varieties of the red gendola (Basella rubra L.) and white gendola (Basella alba L.). Saponin is one of the secondary metabolites from plants gendola. Appropriate planting medium is also a prerequisite of success, especially crop cultivation in containers. The purpose of this study was to investigate the effect and compare the composition of growing media on growth and saponin content in two varieties of plants gendola.The study was conducted in a plastic house agriculture Faculty of University orchard trial Trunojoyo Madura University Madura College of Agricultural Experiment Garden Trunojoyo Madura which lies at an altitude of ± 3 meters above sea level. The study began in November 2011 until Februari 2012. The method used was a factorial experiment based Randomized Design (CRD) with three replicates consisting of two treatment factors, the first factor is gendola different varieties of plants and the second factor is the combination of different growing.The result showed that the treatment plant varieties and combinations of place influende on plant length, leaf number, leaf area, all part plant fresh weight and all part plant dry weight. Red gondolas varieties yield components of growth, biomass weightand content of saponins in the leaves is high. Growing composition 1 : 1 (½ sections of land: ½ cow manure) gave the highest growth component in plant fresh weight and all part plant dry weight. Treatment plant varieties and combination of composition of saponin in the leaves but a very real influence on each treatment factor. The highest saponin content of the red varieties while growing composition 2 : 1 (2/3 parts soil : 1/3 cow manure) and the planting composition 1 : 2 1/3 part of land : 2/3 cowmanure) gives the value highest. Control treatment is growing composition 1: 0 (1part soil : cow dung manure 0) gives the lowest value on the saponin content of leaves.